But Someone Was Right There: An Examination of How Third-Party Presence Is Associated With Rape and Sexual Assault Victim Help-Seeking Behavior and Reports to Police - Powers Mondragon, Hailey (Violence against women, 2024)
This research evaluates whether third-party presence is associated with rape and sexual assault (RSA) victims help-seeking and reporting to police, addressing a gap in the literature about how the presence of a third-party is associated with victim behavior. This research uses secondary data from the National Crime Victimization Survey (NCVS). Findings indicate that third-party presence has no statistically significant association with help-seeking and marginal significance with police reporting. This research focuses on third-party presence as a precursor to understanding victim help-seeking behaviors and reports to police. This research raises questions about the expected role of third parties in RSA victimizations.